A multi-omic dissection of molecular hallmarks of accelerated aging in schizophrenia - DongDong Qi; Peng Liu; YiMeng Wang; XuGuang Tai; ShiFa Ma; Yue Wang (Scientific Reports)
Abstract Schizophrenia, a pervasive mental health condition, poses a global challenge to individual well-being. The intricate interplay of schizophrenia with the aging process is characterized by a shortened lifespan, underscoring the urgent need for an in-depth exploration of the underlying biological mechanisms that contribute to the unique aging trajectory within this specific patient population. Currently, this crucial aspect remains largely unexplored. To bridge this knowledge gap, in the present study, serum samples from of 29 subjects with schizophrenia were analysed via liquid chromatography-mass spectrometry (LC-MS) and compared with those of 30 nonpsychiatric controls. This exploratory analysis of circulating blood serum, albeit based on a limited sample size, provides valuable insights into the significantly altered molecular pathways linked to schizophrenia and clarifies the unique aspects of aging in the context of this particular disease. The data presented in this study constitute a compilation of molecular alterations associated with schizophrenia across the human lifespan. By distinguishing between schizophrenia patients and nonpsychiatric controls, we identified a panel of 342 differentially abundant metabolites and 544 differentially expressed proteins. Our pathway enrichment analysis was focused primarily on histone acetylation, the Wnt/β-catenin signaling pathway, the dopamine receptor signaling pathway, and fatty acid beta-oxidation, highlighting their pivotal roles in schizophrenia. Furthermore, we conducted a co-occurrence analysis of these metabolites and proteins, aiming to elucidate their connection with accelerated aging processes. This analysis revealed the involvement of metabolic pathways crucial for lipid metabolism, such as the peroxisome and peroxisome proliferator-activated receptor (PPAR) signaling pathways, as well as neurotransmitter-related metabolic pathways influencing tryptophan metabolism and the dopaminergic synapse pathway. The findings significantly increase our understanding of the intricate molecular mechanisms underlying schizophrenia and its co-occurring comorbidities across the spectrum of aging, providing insights into the dynamics of the progression of this complex disorder. However, this study has certain limitations, particularly the lack of its findings and the relatively small sample size, especially in the proteomic analysis.